Snow Lion - McPhail, David (U.S.A, 1983)
Lion, finding the jungle too hot for comfort, visits the mountains and falls in love with the cold fluffy white snow that covers the ground here.
Keywords: Lions--Fiction; Snow--Fiction; Jungle Animals--Fiction